2008
DOI: 10.1186/1472-6920-8-3
|View full text |Cite
|
Sign up to set email alerts
|

Can teaching agenda-setting skills to physicians improve clinical interaction quality? A controlled intervention

Abstract: Background: Physicians and medical educators have repeatedly acknowledged the inadequacy of communication skills training in the medical school curriculum and opportunities to improve these skills in practice. This study of a controlled intervention evaluates the effect of teaching practicing physicians the skill of "agenda-setting" on patients' experiences with care. The agenda-setting intervention aimed to engage clinicians in the practice of initiating patient encounters by eliciting the full set of concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 27 publications
3
44
0
4
Order By: Relevance
“…A broad overview of potential discussion topics is constructed The rest of the consultation is structured based on the shared agenda 3.1.3. Negotiating and prioritizing This theme was described as an often-neglected aspect of agenda setting [10,12,[81][82][83]. Where there is disagreement between the patient and clinician's agenda, or where the time available for the consultation is insufficient to cover all agenda items, the agenda is structured through prioritizing [12,81,82].…”
Section: Clinician Agendamentioning
confidence: 99%
“…A broad overview of potential discussion topics is constructed The rest of the consultation is structured based on the shared agenda 3.1.3. Negotiating and prioritizing This theme was described as an often-neglected aspect of agenda setting [10,12,[81][82][83]. Where there is disagreement between the patient and clinician's agenda, or where the time available for the consultation is insufficient to cover all agenda items, the agenda is structured through prioritizing [12,81,82].…”
Section: Clinician Agendamentioning
confidence: 99%
“…It has also been integral to innovations in medical interviewing, such as the 'four-habits model' [26,36] and the 'establishing-focus protocol' [16,21,37]. In addition to reducing the incidence of unmet concerns [2], up-front agenda pursuit is associated with patient satisfaction [14], improved physician understanding of patients' concerns [12], and a decreased incidence of late-emerging concerns [8,38]. Upfront agenda pursuit does not appear to significantly affect visit length [2,8,21], perhaps because it facilitates effective time management [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, physician educators have long advocated communication strategies related to a process frequently referred to as 'agenda setting' [14][15][16][17], or more broadly as 'agenda mapping' [18,19]. Of course, an initial strategy is soliciting patients ' chief complaints with open-ended question formats such as "What can I do for you?"…”
Section: Introductionmentioning
confidence: 99%
“…16,50 And, importantly, medical education research has shown that these communication skills can be taught, learned, and put into practice by trainees and physicians. [51][52][53] Teaching communication skills. Medical educators have used a variety of techniques for teaching communication skills, including simulation with feedback to improve performance; clinical skills demonstration, in which an expert models a behavior and then learners practice the skills; skills intensives, in which groups of physicians meet for one to five days (typically off-site) to learn and practice skills in small groups; peer coaching, in which on-site faculty work with peers to help them improve skills; interviewing rounds, in which a team of clinicians goes to the bedside, interviews an inpatient, and "debriefs" the encounter; and stop-action videotape review, in which a facilitator offers concrete and specific feedback on an individual's videotaped interviewing performance.…”
Section: Training In Communication Skillsmentioning
confidence: 99%